The funky fresh juice book - Vale, Jason (Juice Master Publications, 2011)
Juice Master to the stars and number 1 best-selling author Jason Vale has squeezed over 100 funky 'n' fresh juice and smoothie recipes into this latest book. There's something for Gym Bunnies and a Kids Corner, as well as a Dr. Juice section covering various health conditions and giving specific juices and smoothies for: high blood pressure, asthma, hay fever, psoriasis, arthritis, diabetes, digestion and, many more. Warm up your juicer, dust off your blender and brace your taste buds for the most mouth-wateringly tantalizing fruit and veggie fusions ever created. This book includes a special 'Celebrity Juice' section, with juice and smoothie concoctions from Katie Price, Beverley Knight and other 'celebrity juicers'